Information Technology and Inclusive Digital Transformation: The Necessity of Legal Reform in the Digital Era (Universitas Terbuka, 2025)
Digital transformation has become a primary driver of social and economic change in the modern era, including within legal systems. However, the success of digital transformation largely depends on the principle of inclusivity, which ensures legal access and protection for all segments of society. This study explores the urgent need for legal reform to ensure the law remains relevant, inclusive, and effective in addressing challenges arising from digital innovation, including data governance, cybersecurity, and digital inclusion, while identifying normative constraints and regulatory weaknesses that hinder the realization of fair and inclusive digital transformation. Employing normative legal research through statutory and conceptual approaches, this paper analyzes the limitations of existing legal instruments, particularly in Indonesia, in accommodating evolving digital realities. Findings indicate that Indonesia’s legal system continues to face regulatory fragmentation, lack of recognition of digital rights as fundamental human rights, and insufficient public participation mechanisms in digital policy formulation. Therefore, comprehensive legal reform is necessary, encompassing substantive legal updates, institutional strengthening, and participatory approaches to realize just, inclusive, and sustainable digital governance. This article recommends policymakers integrate the principle of inclusivity as a fundamental foundation in the national digital legal reform agenda.